2002
DOI: 10.1046/j.1471-4159.81.s1.40_12.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetyl cysteine protects against injury in animal model of transient focal cerebral ischemia

Abstract: Ischemic cerebrovascular disease (stroke) is one of the leading causes of death and long‐term disability worldwide (or developing countries). The purpose of this study is to investigate the therapeutic potential of N‐acetyl cysteine (NAC), a precursor of glutathione, and a potent antioxidant, in tissue protection against transient focal cerebral ischemia model in rats. Our laboratory has already demonstrated the efficacy of NAC against induction of proinflammatory cytokines, iNOS, and production of NO in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…47 Sekhon et al also in their study showed preadministration of NAC by protecting cells against free radical damage can attenuate focal cerebral ischemia in an animal model of transient focal cerebral ischemia. 48 Similar to these findings, results of another experimental study revealed administration of ceftriaxone (200 mg/kg) or NAC (150 mg/kg) for 5 days before focal cerebral ischemia by modulating of glutamate transporter expression and normalizing extracellular glutamate concentrations can significantly limit stroke-related damage and increase brain tolerance to ischemia. 49 In a similar vein, Cuzzocrea et al in an experimental study in Mongolian gerbils subjected to cerebral ischemia showed early treatment with NAC (20 mg/kg 30 min before reperfusion and 1, 2, and 6 h after reperfusion) can reduce brain injury induced by transient cerebral ischemia.…”
Section: Discussionsupporting
confidence: 61%
“…47 Sekhon et al also in their study showed preadministration of NAC by protecting cells against free radical damage can attenuate focal cerebral ischemia in an animal model of transient focal cerebral ischemia. 48 Similar to these findings, results of another experimental study revealed administration of ceftriaxone (200 mg/kg) or NAC (150 mg/kg) for 5 days before focal cerebral ischemia by modulating of glutamate transporter expression and normalizing extracellular glutamate concentrations can significantly limit stroke-related damage and increase brain tolerance to ischemia. 49 In a similar vein, Cuzzocrea et al in an experimental study in Mongolian gerbils subjected to cerebral ischemia showed early treatment with NAC (20 mg/kg 30 min before reperfusion and 1, 2, and 6 h after reperfusion) can reduce brain injury induced by transient cerebral ischemia.…”
Section: Discussionsupporting
confidence: 61%